The Effect Of Good Corporate Governance On Company Performance And Company Value In Banking Companies Listed On The Indonesia Stock Exchange In 2018-2020 - Rayi Saraswati, Laras; Kurniawati, Dian; Putri, Amanda (Journal of Accounting and Finance Management, 2024)
This research was conducted to analyze the influence of good corporate governance on company performance and value. The data used in the study are banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study uses a purposive sampling method with a total sample of 18 companies. The analysis test uses SPSS 25 by conducting a classical assumption test, multiple linear regression test, hypothesis test, and determination coefficient test. The results of the study show that good corporate governance influences company performance and good corporate governance affects company value.